Contributions of the Ministry of Endowments and Religious Affairs in the Kurdistan Region of Iraq to the Renewal of Religious Discourse Between 2003 and 2018 - Suleiman, Asst Prof.Dr. Abbas Ali Suleiman; Mustafa, Asst Prof. Dr. Mohamed Khaled Mustafa (Sulaimani Journal for Humanities, 2026)
The researchers aimed through their study titled “Contributions of the Ministry of Endowments and Religious Affairs in the Kurdistan Region of Iraq to the Renewal of Religious Discourse Between 2003 and 2018” to shed light on the contributions of the Ministry of Endowments and Religious Affairs in renewing religious discourse. They demonstrated that the work of renewing religious discourse is of utmost importance, especially in the present era, because all media outlets and social networking sites are readily available to preachers, professionals in Islamic jurisprudence, and religious scholars. The researchers highlighted the efforts made by the ministry in this regard over the past years. They also attempted to identify critical issues by dividing the study into three sections, taking into account the conferences and seminars organized by the ministry as well as the structural changes and legal reforms enacted within the ministry.
Keywords: Ministry of Endowments; Kurdistan Region of Iraq; Renewal of Religious Discourse; Social Communication